2021
DOI: 10.3390/math9202563
|View full text |Cite
|
Sign up to set email alerts
|

Entropy Optimization of First-Grade Viscoelastic Nanofluid Flow over a Stretching Sheet by Using Classical Keller-Box Scheme

Abstract: Nanofluids have better surface stability, thermal absorption, and distribution capacities are produced as heat transfer fluids. In current nanofluid-transport studies, together with the heat transfer mechanisms, entropy reduction in thermo- and non-Newtonian nanofluid models with changing thermophysical characteristics is heavily addressed. The entropy production is examined as thermodynamically stable first-grade viscoelastic nanofluid (FGVNF) flow over a flat penetrable, porous barrier. The uniform porous ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(23 citation statements)
references
References 32 publications
0
23
0
Order By: Relevance
“…Abu-Hamdeh et al computed the quantity of entropy generation when Powell–Eyring nanofluid flows over permeable media in a horizontal surface under thermal jump conditions. Some further explanations and applications of fluid flow along an extending substrate have been discoursed in refs .…”
Section: Literature Reviewmentioning
confidence: 99%
“…Abu-Hamdeh et al computed the quantity of entropy generation when Powell–Eyring nanofluid flows over permeable media in a horizontal surface under thermal jump conditions. Some further explanations and applications of fluid flow along an extending substrate have been discoursed in refs .…”
Section: Literature Reviewmentioning
confidence: 99%
“…Waqas et al [ 15 ] have explored the Marangoni bio-conventional flow of Reiner–Philippoff nanofluid with a melting phenomenon and a non-uniform heat source and sink in the presence of the swimming microorganism. Alazwari et al [ 16 ] have discussed entropy generation using the classical Keller Box technique for first grade viscoelastic nanofluid over a stretching sheet.…”
Section: Introductionmentioning
confidence: 99%
“…The results confirmed that rising thermophoresis and Schmidt number values enhanced the heat transfer coefficient. By changing thermophysical characteristics, entropy reduction in the thermos and non-Newtonian nanofluid models was addressed [40]. Two types of nanofluids, namely Copper-Engine Oil and Zinconium Dioxide-Engine Oil, were considered for the study.…”
Section: Introductionmentioning
confidence: 99%